Delayed Recovery of Visual Acuity after Sphenoorbital Meningioma Surgical Removal: Case Report and Review of the Literature. Is Visual Acuity Recovery Possible after an Initial Decline? - Grassi, Piergiacomo; Strianese, Diego; Mariniello, Giuseppe; Bonavolontà, Giulio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background and Study Aims To report a case of late recovery of visual acuity after surgical removal of a sphenoorbital meningioma (SOM).Materials and Methods A 42-year-old woman was referred for progressive proptosis of the right eye for 5 years. Her best-corrected visual acuity (BCVA) was 10/10 in her right eye and 10/10 in her left eye, and thyroid function tests were negative. Ophthalmic examination showed slight exophthalmos of her right eye, but eye movements and pupillary light reflexes were normal. Intraocular pressure and fundus examination (FE) in both eyes were normal. Computed tomography scan of the orbits showed hyperostosis and an increase in the thickness of the lateral wall of the orbit, volume reduction of the right orbit, the optic canal, and the sphenoidal fissure, edema, and medial displacement of the lateral rectus muscle. We performed coronal orbitotomy and removed the tumor via a frontotemporal-orbitozygomatic approach and lateral orbitotomy.Results  Three hours postoperatively, her right eye was blind with signs of orbital apex syndrome. A high dose of intravenous corticosteroid was then administered. Twenty-four hours postoperatively, BCVA of right eye was motu manu (hand motion), and pupillary light reflexes in the right eye were absent. Five days postoperatively, BCVA allowed counting fingers at 5 m, and ocular motility was partially recovered. Fifteen days postoperatively, BCVA was 1/15, and eye movements were totally recovered. Eight months postoperatively, BCVA was 3/10, pupillary light reflexes were still absent, and FE in the right eye showed a slightly pale temporal half of the optic disc. Twenty months postoperatively, BCVA in the right eye was 7/10.Conclusions Late recovery of visual acuity after sphenoorbital meningioma removal may be possible despite an initial decline.
Keywords: recovery of visual acuity; sphenoorbital meningioma; visual outcome